COMPARATIVE ANALYSIS OF THE SUBJECTIVE WELL-BEING OF THE BALTIC COUNTRIES' INHABITANTS IN THE CONTEXT OF ECONOMIC DEVELOPMENT - Lonska, Jelena; Komarova, Vera (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Since the Baltic countries have joined the European Union, the value of personal satisfaction with life has fluctuated – decreased or increased – along with GDP per capita until the crisis, i.e. until 2009; afterwards, the nature of this dependency started to change across the countries. The novelty of the current research study is the analysis of the people's SWB dependence upon the economic development indicators in the Baltic countries after their accession to the EU, conducted in the context of the results of previous research studies on the topic. The research aim is to review theoretical research studies on the interrelation of people’s SBW and economic development of the country, as well as to analyse the situation in Latvia, Lithuania, and Estonia. The following research methods were applied: the monographic method and regression analysis. The findings of the research study showed that Estonia was the leader among the three Baltic countries in all the economic development indicators considered, whereas Latvia was behind in all the indicators; moreover, the level of personal satisfaction with life was the highest in Estonia, although, as the results of the regression analysis demonstrated the SWB of people in Estonia was the least dependent on the economic development indicators.